The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1971
DOI: 10.1007/bf02890762
|View full text |Cite
|
Sign up to set email alerts
|

Protection of dietary polyunsaturated fatty acids against microbial hydrogenation in ruminants

Abstract: Polyunsaturated fatty acids are normally hydrogenated by microorganisms in the rumen. Because of this hydrogenation ruminant triglycerides contain very low proportions of polyunsaturated fatty acids. A new process is described whereby polyunsaturated oil droplets are protected from ruminal hydrogenation by encapsulation with formaldehyde-treated protein. The formaldehyde-treated protein resists breakdown in the rumen thereby protecting the fatty acids against microbial hydrogenation. When these protected oils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
2

Year Published

1973
1973
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(60 citation statements)
references
References 13 publications
2
56
0
2
Order By: Relevance
“…The esterified fatty acid content of each fraction was determined by the method of Stern and Shapiro (1953).…”
Section: (D) Analytical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The esterified fatty acid content of each fraction was determined by the method of Stern and Shapiro (1953).…”
Section: (D) Analytical Techniquesmentioning
confidence: 99%
“…Following the earlier discovery that formalin treatment prevents microbial degradation of protein in the rumen (Ferguson et al 1967), it has been demonstrated recently that the feeding of large quantities of polyunsaturat ed oil particles coated with formalin-treat ed casein (protected lipid) gives rise to marked increases in the polyunsaturat ed composition of milk (Scott et al 1971). These particles appear to be inert in the rumen and therefore relatively large amounts can be ingested without risk of inducing the ruminal stasis commonly observed when large quantities of unprotected lipid are fed to cows .…”
Section: Introductionmentioning
confidence: 99%
“…A commercial salt of fatty acids(MEG) was used in the control diet(MEG) to make all diets iso-energetic and iso-oil. Concentration of formaldehyde in whole linseed reached 4% on a protein basis, which meets the minimum recommendation of 2% made by Scott et al(1971). Treatment of linseed was carried out by adding 300g of formalin per kg of whole linseeds to create pH reversible methylene bridges within the seed.…”
Section: Animals and Dietsmentioning
confidence: 82%
“…Reductions have been demonstrated in fibre and organic matter digestion, methanogenesis, ammonia concentrations and acetate:propionate value (Devendra and Lewis, 1974;Palmquist and Jenkins, 1980). Therefore, various methods such as formaldehyde-treated emulsions of fat in proteins (Scott et al, 1971), calcium soaps (Jenkins and Palmquist, 1982), heat treatment (Tice et al, 1994), fatty acyl amides (Fotouhi and Jenkins, 1992), the crystalline hydrogenated fat (Elliott et al, 1994) and feeding whole oilseeds (Scollan et al, 2001) for protecting fat sources from rumen metabolism, which offers the possibility that fat sources fed in such a form may interfere less with rumen metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The feeding of polyunsaturated lipid supplements protected from ruminal degradation (Scott et al 1971;Cook et al 1972b) results in ruminant adipose tissue and milk fat containing an increased proportion of polyunsaturated fatty acids particularly linoleic acid but little is known about the effects of prolonged supplementation on such changes or about changes after the supplement has been withdrawn. Accordingly, the present experiment was conducted to monitor changes in total body fat and in the proportion of linoleic acid during and after feeding a polyunsaturated supplement to sheep.…”
Section: Introductionmentioning
confidence: 99%